Flow characteristic investigation of a novel power-augmented water kinetic turbine for energy capturing from river / Christopher Clement Rusli - Christopher Clement, Rusli (2021)
Fossil fuel power plants still dominate world electricity generation. 38% of the world’s electricity generation is coal, and another 23% is natural gas. Fossil power plants impact a lot on pollutant emissions. Therefore, renewable energy needs to be developed to reduce this effect. Renewable energy uses an available energy source that automatically recharges naturally—the energy sources such as sun, wind, water, Earth’s heat, and plants. One of the water sources available is a river, which can generate electricity in rural areas. The hydrokinetic turbine is used to capture the available energy from the river. A lot of studies show the availability to capture water energy using a kinetic turbine. However, the efficiency of the hydrokinetic turbine is relatively low. Thus, this study is carried out to observed the augmentation design for the hydrokinetic turbine. The vertical axis turbine two-blade with NACA0021 airfoil profile will be used for this study. The augmentation observed will be a NACA0015 profile with a chord length of 2000 mm and connected with spline tools to create the augmentation profile. Both analytical and numerical methods will be used in this study. The analytical approach is used to approximate the performance of the blade used for the turbine. The numerical method will be used to observed the flow characteristic and the efficiency of the augmentation profile. Three different pitch angles for the augmentation profile—6°, 10°, and 15° are used to enhance the hydrokinetic turbine’s performance. The hydrokinetic turbine has a baseline performance of 0.397 at TSR is equal to 2.58. The augmentation profile achieved a 77.33% performance improvement with a power coefficient value of 0.704 at TSR is equal to 3.0. The positioning of the turbine is also observed because it affects the performance as well. This study finds that the positioning of the turbine can slightly improve the performance and worsen the performance too. The power coefficient reaches the highest of 0.712 when the turbine slightly moved from the initial position. In conclusion, this study proves the significant impact of the augmentation implemented in the vertical-axis hydrokinetic turbine. The improvement of power coefficient reaches as high as 79.34% compared to the bare turbine.